Arquitetura e solidão: John Hejduk em Berlim - Passaro, Lais Bronstein (Risco - Journal of Architecture and Urbanism, 2003)
This article intends to analyse the architectural projects of John Hejduk for Berlin, which were elaborated for the International Building Exhibition - IBA. As refined thought constructions, such projects concentrate topics directly connected with the debate of those years, related with the more consolidated criticism of the Modern Movement. Hejduk's work represents one of the many streams of such criticism, and leads to an unconventional architectonic understanding, promoting displacements in traditional relationships of theory-practice and subject-object. In that way, better than submerge in the poetic world of his many structures, we will try here to find those suggested inflections through Hejduk's proposals for architecture and the city, and their complicity with the Exposition's specific context.